Coronal Hamate Fractures with Carpometacarpal Dislocation Treated Effectively Using Headless Compression Screws with Percutaneous Pinning Fixation by Using the 2-Directional Approach: A Report of 2 Cases. Issue 2 (April 2020) - Shimizu, Hirokazu; Matsuhashi, Tomoya; Fukushima, Akira; Menjo, Yusuke; Hojo, Yoshihiro; Iwasaki, Norimasa
Abstract : Case: Coronal shear fractures of the hamate are relatively rare injuries. Surgical intervention is recommended for displaced fractures. However, there is no established surgical procedure for the displaced coronal shear fractures of the hamate. Therefore, we present 2 cases of the displaced coronal hamate fracture with metacarpal dislocations, which were successfully managed with open reduction and internal fixation, using the headless compression screw by the 2-directional approach. Conclusion: Our procedure ensured that the screw's distal end captured the hamate hook, and the displaced bone fragments were reduced considerably in both cases.